Safety and efficacy of an ultra low dose fluoroscopic protocol for chronic total occlusion recanalization. Issue 5 (1st March 2023) - Bacci, Elodi; Chiarito, Mauro; Sanz‐Sanchez, Jorge; Leone, Pier Pasquale; Gohar, Aisha; Novelli, Laura; Kovacic, Mihajlo; Regazzoli, Damiano; Reimers, Bernhard; Contorni, Francesco; Ghionzoli, Nicolò; Cameli, Matteo; et al.
Abstract: Background: Chronic total occlusion (CTO) revascularization is a major source of radiation for both patients and physicians. Therefore, efforts to minimize radiation during CTO percutaneous coronary intervention (PCI) are highly encouraged. Aims: To evaluate the impact of an Ultra Low fluoroscopic Dose Protocol (ULDP), based on 3.75 frames per second for the fluoroscopy and 7.5 frames per second for the cine acquisition, during CTO PCI. Methods: One hundred fifty consecutive patients who underwent CTO PCI were retrospectively enrolled. Eighty‐five underwent standard dose protocol (SDP) and 65 ULDP. Radiation exposure and acute clinical outcomes were compared between groups. Results were stratified according to lesion complexity. Results: Patients undergoing ULDP, as compared to those undergoing SDP, showed a significant reduction of kerma area product, both for simple lesions (6861.0 vs. 13236.0 mGy × cm 2 ; p  = 0.014) and complex lesions (CL) (8865.0 vs. 16618.0 mGy × cm 2 ; p  < 0.001). Similarly, Air Kerma (AK) was lower when ULDP was used (1222.5 vs. 2015.0 cGy in SL, p  = 0.134; 1499.0 vs. 2794.0 cGy in CL, p  < 0.001). No significant differences were reported regarding procedural success and in‐hospital major adverse cardiovascular events between groups. Notably, there was not any crossover from ULDO to SDP due to poor quality images. Interestingly, fluoroscopy time, procedural time and contrast volume was significantly lower in patients undergoing ULDP only for CLs. Conclusions: ULDP significantly reduces radiation exposure in the setting of high complexity procedures such as CTO PCI. This reduction seemed to be greater with increased procedural complexity and did not impact acute success or adverse clinical events.